PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Indra Bagus Pranata (Education Journal : Journal Educational Research and Development, 2018)
The purpose of this study is to know simultaneously and partially from three variables, namely human resource development (X1), organizational culture (X2) and motivation (X3) on employee performance (Y); and which variables are dominant. This study uses assessment method that is research that consider to explain the status of variables studied and the relationship between one variable with other variables and recommendations hypothesis that has been formulated. This research use Likert scale, while data processing with doubled linear regression technique. The results of the analysis are: 1. Simultaneously, the development of human resources, organizational culture and work motivation that affect the performance of employees; 2. Partially, the development of human resources, organizational culture and work motivation that affect the performance of employees; 3. Organizational culture has a dominant influence on employee performance with other variables.